INDONESIAN ONLINE MEDIA STRATEGY IN PREVENTING ISLAMOPHOBIA DURING PANDEMIC ERA (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
Online media has an important rules in giving informastion during pandemic era like today. This research was conducted as an effort to look at Indonesian online media strategies as an effort to prevent Islamophobia. The strategy in this study is examined using SWOT analysis to see the strength, weakness, opportunity, and threat of Indonesian online media. The representation related to Islam in online media through samples from major online media in Indonesia, such as Republika.co.id and Kompas.com. In an effort to answer research, the authors use qualitative methods. The results of this study indicate that the media have different strength, weakness, opportunity, and threat so that the strategies used in making efforts to prevent Islamophobia are also different. Therefore, to prevent Islamophobia through the media, they can utilize the power possessed by the media to disseminate information about Islam accurately without any pressure from any party. Weaknesses and threats that are owned by the media related to the news about Islam can be overcome by utilizing the strengths and opportunities owned by the media so that news about Islam will no longer cause fear in the community and Islamophobia can be stopped by the use of the media. The conclusion of this research shows that through the SWOT strategy analysis can be made several strategies by the media as an effort to prevent islamophobia in Indonesia.